ANALISIS PERENCANAAN PERSEDIAAN KACANG KEDELAI PADA UNIT USAHA PRIMER KOPERASI PRODUSEN TEMPE TAHU INDONESIA DI PALEMBANG - NIRWAN RASYID (Program Studi Magister Manajemen FE Unsri, 2015)
The purpose of this research is to determine the soybean of raw material inventory planning that economical in Primkopti Palembang. After did the experiment, the writer found out a problem, such as Primkopti did not know of total the economist purchase that should they do. The problem is used from the first interviews. The writer use interviews to get the primary data and documentation to get the secondary data. Therefore, the writer purposed to give advice for company that there was a method which could use to determine the total of economist purchase, was economic order quantity (EOQ) method, that would count by the formula that wrote by Yamit (2011). And also to know the total inventory cost that counted by the formula wrote by Buffa and Rakesh (1996). The writer get the results of this research is that Primkopti doesn’t have surplus about soybean of raw materials inventory in 2009, 2010, and 2012. But in 2011, Primkopti has surplus the raw materials.